Mechanisms Underpinning Adaptations in Placental Calcium Transport in Normal Mice and Those With Fetal Growth Restriction - Hayward, Christina E.; McIntyre, Kirsty R.; Sibley, Colin P.; Greenwood, Susan L.; Dilworth, Mark R. (Frontiers in Endocrinology, 2018)
Fetal delivery of calcium, via the placenta, is crucial for appropriate skeletal mineralisation. We have previously demonstrated that maternofetal calcium transport, per gram placenta, is increased in the placental specific insulin-like growth factor 2 knockout mouse (P0) model of fetal growth restriction (FGR) compared to wild type littermates (WTL). This effect was mirrored in wild-type (WT) mice comparing lightest versus heaviest (LvH) placentas in a litter. In both models increased placental calcium transport was associated with normalisation of fetal calcium content. Despite this adaptation being observed in small normal (WT), and small dysfunctional (P0) placentas, mechanisms underpinning these changes remain unknown. Parathyroid hormone-related protein (PTHrP), elevated in cord blood in FGR and known to stimulate plasma membrane calcium ATPase, might be important. We hypothesised that PTHrP expression would be increased in LvH WT placentas, and in P0 versus WTL. We used calcium pathway-focused PCR arrays to assess whether mechanisms underpinning these adaptations in LvH WT placentas, and in P0 versus WTL, were similar. PTHrP protein expression was not different between LvH WT placentas at E18.5 but trended towards increased expression (139%; P=0.06) in P0 versus WTL. PCR arrays demonstrated that four genes were differentially expressed in LvH WT placentas including increased expression of the calcium-binding protein calmodulin 1 (1.6 fold; P<0.05). Twenty-four genes were differentially expressed in placentas of P0 versus WTL; significant reductions were observed in expression of S100 calcium binding protein G (2 fold; P<0.01), parathyroid hormone 1 receptor (1.7 fold; P<0.01) and PTHrP (2 fold; P<0.05), whilst serum/glucocorticoid-regulated kinase 1 (SGK1), a regulator of nutrient transporters, was increased (1.4 fold; P<0.05). Tartrate resistant acid phosphatase 5 (TRAP5 encoded by Acp5) was reduced in placentas of both LvH WT and P0 versus WTL (1.6 and 1.7 fold respectively; P<0.05). Signalling events underpinning adaptations in calcium transport are distinct between LvH placentas of WT mice and those in P0 v WTL. Calcium binding proteins appear important in functional adaptations in the former whilst PTHrP and SGK1 are also implicated in the latter. These data facilitate understanding of mechanisms underpinning placental calcium transport adaptation in normal and growth restricted fetuses.